Reply to “Comments on the Article: Management of Suspected Acute Inflammatory Pancreatopathies in a "Real-World" Setting - A Single-Centre Observational Study” - De Nuzzo, Daniele; Miconi, Alessia; Pierantognetti, Paola (JOP. Journal of the Pancreas, 2015)
No abstract available. Image: University of Rome “Sapienza”. Rome, Italy